The Development of the Clinical Supervisor: An Examination of Theories, Contributing Factors, and Measures - Barker, Keegan (Université d'Ottawa / University of Ottawa, 2014)
The development of competency in clinical supervision is becoming an increasingly important element of training and practice in professional psychology. To assist students in developing supervisory competencies, knowledge of relevant research and effective training methods is required. Three studies were designed to add to the field of supervisor development research. In the first study, I conducted a systematic review to examine the extent to which theoretical models of supervisor development have been used in empirical studies of supervisor development within professional psychology. This study revealed that studies rarely employ theory, and when they do, the Supervisor Complexity Model is the most often used theory, likely because it is the only one with an associated measure, the Psychotherapy Supervisor Development Scale (PSDS; Watkins, Schneider, Haynes, & Nieberding, 1995). Building on the findings of this systematic review, in the second study I conducted a reliability and validity generalization on the PSDS. Reliability and validity generalizations are meta-analytic methods that allow reliability and validity data from a measure to be summarized across studies. Results indicate the PSDS has a history of excellent reliability, and higher scores are found with increased supervisory training and experience, evidence of the scale’s validity. The third study is a meta-analysis of the supervisor development literature, in order to assess the effect sizes of training and experience on supervisory development and self-efficacy. Results indicate that training and experience have significant positive effect sizes, though they do not differ from one another. Based on results from these studies I provide recommendations about: the samples with which the PSDS tool is appropriately used, and how researchers might increase reliability within their own future studies, and evidence based recommendations for competency based education efforts.
Keywords: Clinical supervision; Systematic review; Meta analysis